(untitled) (Journal of Misan Researches, 2020)
The knowledge of the Qur’an was not fully understood except through the interpretation of the Prophet (PBUH), and no one would be able to interpret the Qur’an unless he received that interpretation from the Messenger of God (PBUH) and public and private narratives declaring that Imam Ali (pbuh) received all the revelation and interpretation And knowledge of the Qur’an from the Prophet (PBUH). That is why knowing the style of Imam (PBUH) as the heir of the Prophet’s knowledge teaches us the proper use of the Qur’an and its valuable methods of interpretation. This article examines in the librarian way the way the Imam has interpreted (pbuh) his exegetical types and concludes that the Imam (PBUH) in his statement interprets the Qur’an depending on the ability of the addressee and his requirements, in different ways, such as narration, language, representation and ... It is hoped that this article will be a step, even if it is short, in the way of comprehending the greatest man in Islamic history, Imam Ali (pbuh), and getting to know him more and about his vital role in exegesis. Honor him as befitting him.